Development of SETS e-module on endocrine system material to improve scientific literacy and learning independence of high school students - Mahbengi Niate; Paidi Paidi (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
The level of scientific literacy, learning independence, and student learning outcomes in the endocrine system material are still relatively low. This indicates the need for the development of teaching materials that are able to produce scientific concepts in everyday life and encourage active student participation. This study aims to develop a SETS (Science, Environment, Technology, and Society)-based e-module that is feasible, practical, and effective in improving scientific literacy and learning independence. The study used the Research and Development (R&D) method with the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. The subjects of the study consisted of 64 grade XI MIPA students at SMA Negeri 1 Mlati. Data collection techniques included interviews, questionnaires, and tests, with descriptive and inferential data analysis using MANOVA. The results showed that the SETS-based e-module was feasible, practical, and effective. The MANOVA test showed a significance value of 0.00 (p <0.05), while the N-gain results showed an increase in scientific literacy of 0.320 and learning independence of 0.460, both of which were in the moderate category. The results of this study provide scientific evidence that the application of the SETS approach through e-modules has a positive impact on students' science literacy and learning independence in biology. This study recommends that SETS e-modules can be used as alternative teaching materials in biology learning and opportunities for further research to develop SETS e-modules for other subjects.Abstrak. Tingkat literasi sains, kemandirian belajar, dan hasil belajar siswa pada materi sistem endokrin masih tergolong rendah. Hal ini menunjukkan perlunya pengembangan bahan ajar yang mampu menghasilkan konsep sains dalam kehidupan sehari-hari serta mendorong partisipasi aktif siswa. Penelitian ini bertujuan untuk mengembangkan e-modul berbasis SETS (Science, Environment, Technology, and Society) yang layak, praktis, dan efektif dalam meningkatkan literasi sains dan kemandirian belajar. Penelitian menggunakan metode Research and Development (R&D) dengan model pengembangan ADDIE yang terdiri atas lima tahap: analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian terdiri dari 64 siswa kelas XI MIPA di SMA Negeri 1 Mlati. Teknik pengumpulan data meliputi wawancara, angket, dan tes, dengan analisis data secara deskriptif dan inferensial menggunakan MANOVA. Hasil penelitian menunjukkan bahwa e-modul berbasis SETS tergolong layak, praktis, dan efektif. Uji MANOVA menunjukkan nilai signifikansi 0,00 (p < 0,05), sedangkan hasil N-gain menunjukkan peningkatan literasi sains sebesar 0,320 dan kemandirian belajar sebesar 0,460, keduanya termasuk kategori sedang. Hasil penelitian ini memberikan kontribusi ilmiah berupa bukti bahwa penerapan pendekatan SETS melalui e-modul berdampak positif terhadap literasi sains dan kemandirian belajar siswa pada topik biologi. Penelitian ini merekomendasikan bahwa e-modul SETS dapat dijadikan alternatif bahan ajar pada pembelajaran biologi dan peluang untuk penelitian selanjutnya mengembangkan e-modul SETS pada materi lainnya.